Regulatory Mechanisms Underlying the Differentiation of Neotenic Reproductives in Termites: Partial Release From Arrested Development - Oguchi, Kohei; Maekawa, Kiyoto; Miura, Toru (Frontiers in Ecology and Evolution, 2021)
Eusocial insects exhibit reproductive division of labor, in which only a part of colony members differentiates into reproductives. In termite colonies, the division of labors is performed among multiple types of individuals (i.e., castes), such as reproductives, workers, and soldiers to organize their society. Caste differentiation occurs according to extrinsic factors, such as social interactions, leading to developmental modifications during postembryonic development, and consequently, the caste ratio in a colony is appropriately coordinated. In particular, when the current reproductives die or become senescent, some immature individuals molt into supplementary reproductives, also known as “neotenics,” that take over the reproductive task in their natal colony. Neotenics exhibit variety of larval features, such as winglessness, and thus, immature individuals are suggested to differentiate by a partial release from arrested development, particularly in the reproductive organs. These neotenic features, which have long been assumed to develop via heterochronic regulation, provide us opportunities to understand the developmental mechanisms and evolutionary origin of the novel caste. This article overviews the accumulated data on the physiological and developmental mechanisms that regulate the neotenic differentiation in termites. Furthermore, the evolutionary trajectories leading to neotenic differentiation are discussed, namely the acquisition of a regulatory mechanism that enable the partial release from a developmentally arrested state.